Stability, compatibility and performance improvement of SrCo0.8Fe0.1Nb0.1O3−δ perovskite as a cathode for intermediate-temperature solid oxide fuel cells. (16th February 2017) - Wang, Shizhuo; Jin, Fangjun; Li, Lei; Li, Rongrong; Qu, Baoping; He, Tianmin
Abstract: SrCoO3− δ is a mixed ionic-electronic conductor with multiphase. The structural instability, chemical and thermal incompatibility with the standard electrolytes in this material restrict its widespread applications as electrochemical devices. Here we report the characterization and performance improvement of SrCo0.8 Fe0.1 Nb0.1 O3− δ (SCFN) perovskite as a potential cathode material for intermediate-temperature solid oxide fuel cells (IT-SOFCs). The SCFN material exhibits good chemical compatibility with both La0.9 Sr0.1 Ga0.8 Mg0.2 O3− δ (LSGM) and Gd0.1 Ce0.9 O1.95 (GDC) electrolytes at 950 °C for 10 h. Fe and Nb co-doping significantly improves the structural stability, thermal expansion compatibility, and electrochemical performance of the SCFN material as compared to the undoped SrCoO3− δ and Fe-doped SrCo0.8 Fe0.2 O3− δ (SCF). The introduction of GDC further improves the thermal compatibility and electrochemical performance of the SCFN–GDC composite cathodes, where the thermal expansion coefficients decrease from 24.5 × 10 −6 K −1 for SCFN to 16.8 × 10 −6 K −1 for SCFN–50GDC between 30 and 950 °C in air, the corresponding area specific resistances are 0.091 and 0.075 Ω cm 2 at 700 °C, respectively. The SCFN and its composites reveal some promising aspects of applications in IT-SOFCs. The SCFN–GDC composites provide a trade-off between TEC and electrochemical performance for application as IT-SOFC cathode materials. Graphical abstract: Highlights: Performance of SCFN as LaGaO3 -based IT-SOFC cathode is studied and greatly improved. SCFN is chemically compatible with both LSGM and GDC electrolytes at 950 °C for 10 h. SCFN exhibits good structural stability, electrochemical performance and stability. Adding GDC into SCFN improves thermal compatibility and electrochemical performance.